2008
DOI: 10.1203/pdr.0b013e31816d9117
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functional and Protective Actions of Preconditioning With Hypoxia, Cobalt Chloride, and Desferrioxamine Against Hypoxic-Ischemic Injury in Neonatal Rats

Abstract: ABSTRACT:Preconditioning with hypoxia and hypoxia-mimetic compounds cobalt chloride (CoCl 2 ) and desferrioxamine (DFX) protects against hypoxic-ischemic (HI) injury in neonatal rat brain. We examined long-term functional and protective actions of preconditioning induced by hypoxia, CoCl 2 and DFX in a neonatal rat model of HI. Postnatal day six rat pups were exposed to preconditioning with hypoxia (8% oxygen) or injections of CoCl 2 , DFX or saline vehicle and 24 h later rats underwent HI or sham surgery. Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 41 publications
5
32
0
Order By: Relevance
“…The extent of injury that occurred in the current study is consistent with previous studies using the Rice-Vannucci model [19][20][21], which causes permanent ischemia in the ipsilateral hemisphere of the brain and hypoxia, but no damage in the contralateral hemisphere. Here we observed injury in the ipsilateral hemisphere affecting various brain regions including cortex, hippocampus and striatum.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The extent of injury that occurred in the current study is consistent with previous studies using the Rice-Vannucci model [19][20][21], which causes permanent ischemia in the ipsilateral hemisphere of the brain and hypoxia, but no damage in the contralateral hemisphere. Here we observed injury in the ipsilateral hemisphere affecting various brain regions including cortex, hippocampus and striatum.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have demonstrated neuroprotective roles for HIF-1a which could be explained by the transcription of many HIF-1 target genes involved in various cellular adaptive processes such as changes in glucose transport and metabolism, angiogenesis and neurogenesis [20,23]. Hypoxic treatment can increase expression of HIF-1, HIF-1 target genes and PHD2 [17,32,33], and recently the protective actions of hypoxic preconditioning were shown to be dependent on HIF-1a [16].…”
Section: Discussionmentioning
confidence: 99%
“…Because many studies have shown that the CoCl 2 preconditioning can reduce the ischemia/hypoxia injury in many fields [23,24], our study focused on tolerance time and the disappearance of PS in hypoxia preconditioning mice which were treated with CoCl 2 before hypoxia exposure. Through this study we further clarified the role of HIF-1 in hypoxia tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, CoCl 2 induces a hypoxiamimicking response by impairing the binding of von Hippel-Lindau protein with HIF-1a (Yuan et al 2003) causing the stabilization of HIF-1a and preventing its degradation by the proteasome. CoCl 2 has been recently used for preconditioning treatment and protection against hypoxicischemic injury in neonatal rats (Jones et al 2008).…”
Section: Introductionmentioning
confidence: 99%